210Po concentration in desulfurized waste water of coal-fired power plant. Issue 1 (2nd January 2019) - Liu, Ruirui; Wang, Chuangao; Luo, Zhiping; Pan, Jingshun; Zhao, Tianyu
ABSTRACT: The concentration of 210 Po in the desulfurized waste water can be affected by the operation of the wet desulfurization system in the coal fired power plant (CFP). However, this correlation is poorly studied and documented in current literature. The aim of this study was to report 210 Po concentration level in desulfurized waste water from a CFP using wet desulfurization system. The average concentration of 210 Po in the waste water samples from wet desulfurization system was measured 2.4 ± 0.3E-3 Bq/L, 4 times higher than the concentration of 210 Po in our control samples (sea water), which is 6.1 ± 1.4 E-04 Bq/L. The annual total discharge of 210 Po by the waste water of desulfurization system was estimated to be 7.03 × 10 8 Bq/GWa, which is much higher than the total release of 210 Po in air from stack of a modern CFP.